(untitled) (Scientific journal of the Fergana State University, 2024)
In this work, the esterification reactions of some aromatic acetylene alcohols with aliphatic (saturated and unsaturated) and aromatic carboxylic acids were studied for the first time. The process was carried out in the presence of a concentrated H2SO4 catalyst in a benzene solution and esters with high biological activity were synthesized. The influence of the structure, nature and chemical activity of selected alcohol and acid molecules on the course of the reaction and the yield of the product was analyzed. The most optimal conditions for managing and monitoring the esterification process were found and reaction mechanisms were proposed. The synthesized esters have been identified, and their partial constants, structure, purity and composition have been proven using modern physicochemical methods.